Metodologiczna charakterystyka współczesnych teorii nauczania i literatury (zarys problematyki) = Methodological characterization of contemporary theories on teaching and learning literature (outline of problems) - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author singles out two phases in the evolution of literary didactics: A prior-theoretical phase and a theoretical one. In the first phase literary didactics did not go beyond the essence of actual social experience, gathered and generalized facts and systematized current knowledge about processes of teaching and learning literature. In the second phase, the theoretical one, the researcher's practice goes beyond the limits of actual social experience and begins to form theories which remain in connection with this experience.
Keywords: literatura; nauczanie; teoria literatury